STRENGTHENING TEACHERS' PEDAGOGICAL COMPETENCE IN THE DIGITAL ERA: AN INTERNATIONAL COMMUNITY ENGAGEMENT COLLABORATION - Rosidah, Cholifah Tur; Cholifah Tur Rosidah; Parichat Pimon; Reza Rachmadtullah; Akhmad Qomaru Zaman; Imas Srinana Wardani; Rarasaning Satianingsih; Prayogo (Universitas PGRI Adi Buana Surabaya, 2025)
This international community service program was conducted from June 2 to 4, 2025, as a collaboration between lecturers from the Master of Primary Education program and lecturers from Maejo University, Thailand, at SD ICP Al Falah Darussalam 2, Tropodo, Waru, Sidoarjo. The theme of the program was Strengthening Teachers' Pedagogical Competence in the Digital Era. The activity aimed to enhance teachers’ pedagogical competence in responding to the challenges of the digital age. The methods employed included interactive training sessions, group discussions, and guided hands-on practice using digital technology. The results indicated a high level of participant enthusiasm, improved understanding of digital pedagogy, and increased motivation among teachers to integrate technology into their teaching practices. This initiative demonstrates that international collaboration can significantly strengthen local capacity in developing teacher competence for the digital era